Four new species of monhysterids (Nematoda: Monhysterida) from mangroves of the Mekong river estuaries of Vietnam - Gagarin, Vladimir G.; Thanh, Nguyen Vu (Academia Journal of Biology, 2014)
Four new free-living nematode species of the order Monhysterida from Me Kong River estuaries of Vietnam are described. Thalassomonhystera tenuis sp. nov. resembles to Thalassomonhystera pusilla (Boucher, Heleouët, 1977) but differs from it by the high, isolated labial region, longer outer labial setae, shorter oesophagus, shorter spicules, absence of gubernaculum’s dorso-caudal apophysis and presence of subterminal setae on the tip. Diplolaimelloides elegans sp. nov. resembles to Diplolaimelloides meyli Timm, 1961, but it differs in having longer and slender tail and vulva position located in more anterior body end. Sphaerotheristus supplementatus sp. nov. comes close to Sphaerotheristus parvus Gagarin, Nguyen Vu Thanh, 2006, it differs in having the longer and thinner body and papillae-shaped supplements in males. Terschellingia obesa sp. nov. similar to Terschellingia monohystera Wieser, Hopper 1967 and Terschellingia brevicaudata Ott, 1972, but it differs from T. monhystera in having shorter cephalic setae, others vulva position and absence of oesophagus basal bulb; it also differs from T. brevicaudata in having shorter body, shorter cephalic setae, shorter spicules and presence of one ovary.